Individual capacity-building approaches in a global pharmaceutical systems strengthening program: a selected review - Niranjan Konduri; Megan Rauscher; Shiou-Chu Judy Wang; Tanya Malpica-Llanos (Taylor & Francis Group, 2017)
Background Medicines use related challenges such as inadequate adherence, high levels of antimicrobial resistance and preventable adverse drug reactions have underscored the need to incorporate pharmaceutical services to help achieve desired treatment outcomes, and protect patients from inappropriate use of medicines. This situation is further constrained by insufficient numbers of pharmaceutical personnel and inappropriate skill mix. Studies have addressed individual capacity building approaches of logistics, supply chain or disease specific interventions but few have documented those involving such pharmacy assistants/professionals, or health workers/professionals charged with improving access and provision of pharmaceutical services. We examined how different training modalities have been employed and adapted to meet country-specific context and needs by a global pharmaceutical systems strengthening program in collaboration with a country's Ministry of Health and local stakeholders. Methods Structured, content analysis of training approaches from twelve selected countries and a survey among conveniently selected trainees in Bangladesh and Ethiopia. Results Case-based learning, practice and feedback, and repetitive interventions such as post-training action plan, supportive supervision and mentoring approaches are effective, evidence-based training techniques. In Ethiopia and Bangladesh, over 94% of respondents indicated that they have improved or developed skills or competencies as a result of the program's training activities. Supportive supervision structures and mentorship have been institutionalized with appropriate management structures. National authorities have been sensitized to secure funding from domestic resources or from the global fund grants for post-training follow-up initiatives. The Pharmaceutical Leadership Development Program is an effective, case-based training modality that motivates staff to develop quality-improvement interventions and solve specific challenges. Peer-to-peer learning mechanisms than traditional didactic methods was a preferred intervention among high level government officials both within country and between countries. Conclusion Interventions must involve local institutions in the design and delivery of content for both pre-service and in-service training as well as web-based methods where feasible. Such efforts would meet the changing demand in the pharmaceutical system, and promote the ownership of the human capacity development interventions. The cost-effective partnership with universities demonstrate that competency based pre-service training will prepare the future pharmaceutical workforce with a critical foundation of knowledge and skills required to meet the growing demand for patient-centered pharmaceutical services in resource-constrained countries.